2018
DOI: 10.3389/fphar.2018.00902
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Nuciferine and N-Nornuciferine, Two Major Alkaloids From Nelumbo nucifera Leaves, in Rat Plasma and the Brain

Abstract: The leaf of the lotus (Nelumbo nucifera) is a natural plant resource used as both food and herbal medicine (He-Ye) in China. Alkaloids are considered the major bioactive compound of the herb and exhibit various biological activities, including anti-hyperlipidemia, anti-obesity, anti-inflammatory, and anti-hyperuricemic effects. Nuciferine (NF) and N-nuciferine (N-NF) are two major alkaloids found in the herb. In the present work, the plasma and brain pharmacokinetics of the two compounds were investigated afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…A few studies on one or two alkaloid of lotus leaf in pharmacokinetic study have been reported (Gu et al, 2014; Xu et al, 2015; Geng et al, 2018; Ye et al, 2018). Comparisons of the present work with other reported method are listed in Table 6 in detail: First, compared with consumption of organic solvent in this work, there were less organic solvent in these reports (Xu et al, 2015; Geng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies on one or two alkaloid of lotus leaf in pharmacokinetic study have been reported (Gu et al, 2014; Xu et al, 2015; Geng et al, 2018; Ye et al, 2018). Comparisons of the present work with other reported method are listed in Table 6 in detail: First, compared with consumption of organic solvent in this work, there were less organic solvent in these reports (Xu et al, 2015; Geng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Liriodenine, O-nornuciferin, and armepavine exhibit the activities of antioxidant and antimicrobia antifibrotic (Costa et al, 2010; Weng et al, 2012). In addition, there were only a few reports for pharmacokinetic studies of one or two alkaloid compounds after oral administration of lotus leaf extract (Gu et al, 2014; Xu et al, 2015; Geng et al, 2018; Ye et al, 2018). However, the pharmacokinetic property of one or two alkaloids does not represent the metabolic regulation of the whole lotus leaf in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, it is becoming more and more popular as weight-losing tea in China to reduce the level of lipids in the human body [79]. Studies have shown that alkaloids are the major bioactive compounds in lotus leaves, with nuciferine and N-nornuciferine being the major two [80,81,82]. To evaluate the biosynthesis pathway of alkaloids and its regulation in lotus leaf, several transcriptomic studies were performed [83,84], which revealed that a benzylisoquinoline alkaloids (BIA) biosynthetic pathway and its transcriptional regulation differ in high BIAs lotus compared with low BIAs lotus [84].…”
Section: Genetic and Molecular Studies On The Horticultural Traitsmentioning
confidence: 99%
“…Peak numbers 3,9,12,15,18,20,23,24,25,31 and 36 represent different flavonoids and their derivatives with numerous health beneficial properties including antioxidant, anticancer, anti-inflammatory, antidiabetic and antimicrobial properties [36]. 2-Methoxy cinnamic acid (peak 5, m/z: 178.195) is a bioactive derivative of cinnamic acid and metabolite of tyrosinase inhibitor and had shown anti-inflammatory, antipyretic, and analgesic properties [37].…”
Section: Compounds Profiled By Lc-qtof-ms Analysismentioning
confidence: 99%
“…B; 24 min, 55% B; 28 min, 75% B; and 32 min, 90% B. e final condition was maintained for the next 8 minutes[18].2.6. Statistical Analysis.All experiments were conducted in triplicate, and one-way analysis of variance using Tukey's multiple comparison tests was performed.…”
mentioning
confidence: 99%